TB in healthcare workers in the UK: a cohort analysis 2009–2013. Issue 7 (17th February 2016) - Davidson, Jennifer A; Lalor, Maeve K; Anderson, Laura F; Tamne, Surinder; Abubakar, Ibrahim; Thomas, H Lucy
Abstract : Objectives: To describe the burden of TB in healthcare workers (HCWs) in the UK and determine whether HCWs are at increased risk of TB due to occupational exposure. Methods: Retrospective cohort analysis of national UK TB surveillance and genotyping data between 2009 and 2013. The rate of TB in HCWs compared with non-HCWs to calculate incidence rate ratios stratified by country of birth. Results: 2320 cases of TB in HCWs were notified in the study period, 85% were born abroad. The TB rate in HCWs was 23.4 (95% CI 22.5 to 24.4) per 100 000 compared with 16.2 (95% CI 16.0 to 16.3) per 100 000 in non-HCWs. After stratifying by country of birth, there was not an increased TB incidence in HCWs for the majority of countries of birth, including in the UK-born. Using combined genotyping and epidemiological data, only 10 confirmed nosocomial transmission events involving HCWs were identified between 2010 and 2012. Of these, only two involved transmission to patients. Conclusions: The lack of an increased risk of TB after stratifying by country of birth, and the very few transmission events involving nosocomial transmission in the UK suggests that TB in HCWs in the UK is not generally acquired through UK occupational exposure. The majority of cases in foreign-born HCWs are likely to result from reactivation of latent TB infection (LTBI) acquired abroad, and is not likely to be prevented by BCG vaccination in the UK. Testing and treatment of LTBI in HCWs with exposure to high TB burden countries should be the focus of occupational health prevention activities.